Heuristic Pedagogy As A Training Method For The Creative Individuality Of Students - M.R. Borodina (Genius Journals, 2023)
The article is devoted to the methodology of teaching in the field of conceptual design. The method is aimed at developing the author's individual, figurative approach to the interpretation of the function and form of architecture.
Keywords: creativity; copyright; plagiarism; problem